Cost-effectiveness analysis in the treatment of heavy menstrual bleeding in Spain. (January 2015) - Calaf, J.; Lete, I.; Canals, I.; Crespo, C.; Espinós, B.; Cristóbal, I.
Abstract: Objective: To compare the effectiveness and costs associated with first-line medical treatments for chronic heavy menstrual bleeding (HMB) in Spain. Study design: A cost-effectiveness analysis was conducted comparing the levonorgestrel-releasing intrauterine system (LNG-IUS) with the estradiol valerate/dienogest multiphase oral contraceptive (E2V/DNG), combined oral contraceptives (COC) and progestins (PROG). Study patients were fertile women diagnosed with HMB who initially wished to remain fertile. A Markov model based on reported clinical data and the opinion of a panel of experts was used. The time horizon of the analysis was 5 years. The analysis was conducted from the perspective of the Spanish National Health System (NHS), discounting both costs (€ 2013) and future effects at an annual rate of 3%. One-way sensitivity analyses and probabilistic sensitivity analysis were performed to test the robustness of the results. Results: In the analysis at 5 years, the LNG-IUS was associated with a gain of 0.67, 2.22, and 3.53 symptoms free months (SFM) compared with E2V/DNG, COC and PROG, respectively. LNG-IUS contributed more quality-adjusted life months (QALM) than the other treatment alternatives (+1.74 vs. E2V/DNG, +3.33 vs. COC +3.53 vs. PROG). First-line LNG-IUS treatment resulted in savings of € 583, € 988, and € 1891 vs. E2V/DNG, COC and PROG, respectively. These cost benefits, coupled with the greater clinical benefits in terms of SFM and QALM, show that LNG-IUS is the dominant option (less costly and more effective). Conclusion: LNG-IUS is the medical treatment of choice and cost-saving option for the control of HMB in Spain.